The objective of this research is to evaluate the characteristic of composite board made from coconut fibre, recycled polypropylene (RPP), and bamboo matting layers. The board samples target density was 0,70 g/cm3. The board construction type was core type composite board (three layers). Coconut fiber and RPP were used as core, and bamboo matting was used as face and back layers. RPP was used 50% based on coconut fiber oven dry weight. The bamboo sheet wide is 1 cm and 2 cm, with and without b - Dina SETYAWATI; Yusuf SUDO HADI; Muh. YUSRAM MASSIJAYA; Naresworo NUGROHO (Departemen Hasil Hutan, IPB, 2008)
The objective of this research is to evaluate the characteristic of composite board made from coconut fibre, recycled polypropylene (RPP), and bamboo matting layers. The board samples target density was 0,70 g/cm3. The board construction type was core type composite board (three layers). Coconut fiber and RPP were used as core, and bamboo matting was used as face and back layers. RPP was used 50% based on coconut fiber oven dry weight. The bamboo sheet wide is 1 cm and 2 cm, with and without bark. The bamboo matting layers were used in slope (45˚) and perpendicular (0/90˚) orientation to length of the board. The research results showed that utilization of bamboo matting layers increase the mechanical properties of board. All of composite board made from coir, RPP, and bamboo matting layers fulfill the JIS A 5908 standard in density, thickness swelling after 24 hours of water immersions, and screw holding power. Only composite boards with bamboo matting layers with bark, sheet wide 1 cm, and perpendicular orientation to length of the board fulfill JIS A 5908 1994 standard for veneered particleboard in MOE. However, application of bamboo matting layers without bark is adviced better because more efficient in the raw material using. Keywords: Composites board, coconut fiber, recycled polyprophylene, bamboo matting layers